2007
DOI: 10.1177/1078155207078137
|View full text |Cite
|
Sign up to set email alerts
|

Management of platinum-based chemotherapy-induced acute nausea and vomiting: is there a superior serotonin receptor antagonist?

Abstract: No significant difference exists in the antiemetic efficacy of the three 5-HT(3) antagonists studied in controlling CINV when administered in combination with dexamethasone. Choicce of antiemetic regimen should therefore be based on drug cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…Similarly, an increased prevalence of nausea and vomiting has been reported in women [6,7]. Reasons for this are uncertain, but palliative chemotherapy regimens used for breast and gynecological cancers, which frequently consist of cyclophosphamide and platinum agents, are highly emetogenic [40,41]. Furthermore, past studies have suggested that women may have an increased predisposition for chemotherapy-related nausea and vomiting compared to men [42][43][44].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, an increased prevalence of nausea and vomiting has been reported in women [6,7]. Reasons for this are uncertain, but palliative chemotherapy regimens used for breast and gynecological cancers, which frequently consist of cyclophosphamide and platinum agents, are highly emetogenic [40,41]. Furthermore, past studies have suggested that women may have an increased predisposition for chemotherapy-related nausea and vomiting compared to men [42][43][44].…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we did not differentiate the individual first generation 5-HT 3 RAs used, in part, to simplify the study design, and also based on an earlier report of no significant difference between the antiemetic efficacy of dolasetron, granisetron, or ondansetron in controlling CINV in patients on platinum-based chemotherapy regimens [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Nausea and vomiting can adversely affect patients' quality of life and make it difficult for them to perform their activities of daily living (Bloechl-Daum, Deuson, Mavros, Hansen, & Herrstedt, 2006). Uncontrolled CINV can give rise to medical complications, including poor nutrition, dehydration, electrolyte imbalances, and physical and mental deterioration (Hamadani et al, 2007). In some cases, patients may refuse to continue potentially beneficial treatment regimens because of treatment-associated nausea and vomiting (Hamadani et al).…”
Section: Impact and Incidence Of Chemotherapyinduced Nausea And Vomitingmentioning
confidence: 98%